A multi-network comparative analysis of whole-transcriptome and translatome reveals the effect of high-fat diet on APP/PS1 mice and the intervention with Chinese medicine - Gao, Wenya; Zhou, Junyi; Gu, Xinru; Zhou, Yanyan; Wang, Linna; Si, Nan; Fan, Xiaorui; Bian, Baolin; Wang, Hongjie; Zhao, Haiyu (Frontiers in Nutrition, 2022)
Different studies on the effects of high-fat diet (HFD) on Alzheimer's disease (AD) pathology have reported conflicting findings. Our previous studies had shown HFD have significant impact on both inflammation and cognition on AD. To gain more insights the involvement of HFD, we performed whole-transcriptome sequencing and ribosome footprints profiling. Combined with competitive endogenous RNA analysis, the transcriptional regulation mechanism of HFD on AD mice was systematically revealed from RNA level. Mmu-miR-450b-3p and mmu-miR-6540-3p might be involved in regulating the expression of Th and Ddc expression. MiR-551b-5p regulated the expression of a variety of genes including Slc18a2 and Igfbp3. Our data had shown the close connection between alterations of transcriptome and translatome under the effect of HFD, emphasizing the roles of translational and transcriptional regulation were relatively independent. The profiled molecular responses in current study might be valuable resources for advanced understanding of the mechanisms underlying HFD effect on AD.